Access to a Canadian provincial integrated trauma system: A population-based cohort study. Issue 4 (April 2015) - Kuimi, Brice L. Batomen; Moore, Lynne; Cissé, Brahim; Gagné, Mathieu; Lavoie, André; Bourgeois, Gilles; Lapointe, Jean; Jean, Sonia
Abstract: Background: Access to specialised trauma care is an important measure of trauma system efficiency. However, few data are available on access to integrated trauma systems. We aimed to describe access to trauma centres (TCs) in an integrated Canadian trauma system and identify its determinants. Methods: We conducted a population-based cohort study including all injured adults admitted to acute care hospitals in the province of Québec between 2006 and 2011. Proportions of injured patients transported directly or transferred to TCs were assessed. Determinants of access were identified through a modified Poisson regression model and a relative importance analysis was used to determine the contribution of each independent variable to predicting access. Results: Of the 135, 653 injury admissions selected, 75% were treated within the trauma system. Among 25, 522 patients with major injuries [International Classification of diseases Injury Severity Score (ICISS < 0.85)], 90% had access to TCs. Access was higher for patients aged under 65, men and among patients living in more remote areas ( p -value <0.001). The region of residence followed by injury mechanism, number of trauma diagnoses, injury severity and age were the most important determinants of access to trauma care. Conclusions: In an integrated, mature trauma system, we observed high access to TCs. However, problems in access were observed for the elderly, women and in urban areas where there are many non-designated hospitals. Access to trauma care should be monitored as part of quality of care improvement activities and pre-hospital guidelines for trauma patients should be applied uniformly throughout the province.